Be cool, not cruel / Muhammad Nabil Irfan Azhar Hakimin and Abd Rahman Jamaan - Azhar Hakimin, Muhammad Nabil Irfan; Jamaan, Abd Rahman (Academy of Language Studies, 2023)
As one reaches adulthood, most people would think that there is no such thing as bullying anymore since most human beings would be mature and have common sense as they reach a certain age. However, the majority of adults do not realise how bullying still happens even when they are grown up. From online harassment to physical violence, there are few places where bullying has not taken root and begun to cause harm. For this reason, it’s important to explore anti-bullying strategies that can be implemented in various environments to help prevent and manage the threat of bullying. Raising awareness about the issue of bullying is crucial in order to effectively address and prevent it. By educating ourselves and others about the various forms of bullying and their impact, we can take steps to create a safer and more inclusive society for everyone. The objective and purpose of this project are to educate and inform the readers about bullying and raise awareness. Other than raising awareness about the issue, entrepreneurial opportunities can also be achieved. Past research from researchers that study the same topic helped a lot. For the methodology aspect of this project, a market survey was conducted involving 30+ active participants of ages ranging from 15 to 26 and above. The survey conducted is very crucial as the knowledge and new information gained from the form that was answered by many received a lot of different answers that helped the process of finishing the project.